# In each of the fo

We have,

f(x) = 4x4-3x3-2x2+x-7 and g(x) = x-1

Therefore, by remainder theorem when f (x) is divided by g (x) = x – 1, the remainder is equal to f (+1)

Now, f(x) = 4x4-3x3-2x2+x-7

f (1) = 4 (1)4 – 3 (1)3 – 2 (1)2 + 1 – 7

= 4 – 3 – 2 + 1 – 7

= -7

Hence, required remainder is -7.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Division of Polynomials46 mins
Quiz- Test what you Know Part 246 mins
Polynomials- Introduction45 mins
Identities Ke Master Bane47 mins
Quiz- Test what you Know64 mins
Conservation of Energy41 mins
Newton's Second Law46 mins
Pair of Angles29 mins
Newton's Third Law44 mins
Miscellaneous questions42 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x31</sRS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x3RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics